Normobaric oxygen therapy in acute ischemic stroke: A pilot study in Indian patients - Padma M (Annals of Indian Academy of Neurology, 2010)
Purpose: Clinical and radiological assessment of effects of normobaric high-flow oxygen therapy in patients with acute ischemic stroke (AIS). Materials and Methods: Patients with anterior circulation ischemic strokes presenting within 12 h of onset, ineligible for intravenous thrombolysis, an National Institute of Health Stroke Scale (NIHSS) score of >4, a mean transit time (MTT) lesion larger than diffusion-weighted image (DWI) (perfusiondiffusion mismatch), and an evidence of cortical hypoperfusion on magnetic resonance imaging (MRI) were included into the trial. Active chronic obstructive pulmonary disease (COPD), requirement of >3/L min oxygen delivery to maintain SaO2 > 95%, rapidly improving neurological deficits, pregnancy, contraindications to MRI, or unstable medical conditions were excluded. The experimental group received humidified oxygen at flow rates of 10 L/min for 12 h. The NIHSS, modified Rankin Score (mRS), Barthel Index (BI) were measured at 0, 1, 7 day of admission and at 3 months follow-up. MRI with DWI/PWI was performed at admission, 24 h later and at 3 months follow-up. Results: Of 40 patients (mean age = 55.8 years ± 13.2) (range, 26-82), 20 patients were randomized to normobaric oxygen (NBO). The mean NIHSS in NBO and control groups were 14.25 and 12.7 at admission which decreased to 11.6 and 9.5 on the seventh day, and 9.4 and 9.05 at 3 months, respectively. The mean mRS (3.7/3.7) and BI (58.2/53.9) in NBO and control groups improved to 2/2.2 and 73.05/73.8 at the end of 3 months, respectively. Conclusions: NBO did not improve the clinical scores of stroke outcome in Indian patients with AIS.